TOPOLOGICAL ANALYSES OF THE ELECTRONIC DENSITY OF H-NbSe2 COMPLEXES - Alvanh Alem G. Pido (International Engineering Journal For Research & Development, 2022)
Transition metal dichalcogenides are among the emerging two-dimensional materials nowadays due to their unique and extraordinary properties. Niobium Diselenide (NbSe2) is a transition metal dichalcogenide that has been formed by sandwiching one Nb atom with two Se atoms. In this work, we dope H atoms to 1 x 1 x 1 monolayer NbSe2 and performed topological analyses to find the charge transfer and binding mechanism of the resulting H-NbSe2 complexes. Calculations of the binding energies revealed that the strength of interaction is proportional to H coverages in the system. Further, charge redistributions have been observed in the system. Bader charge analysis reveals that the charge transfer is towards the H atoms with a magnitude of up to 1.13 e. Finally, it was revealed that the strength of interaction between the H and NbSe2 depends on where H bonds directly.